Identification of Potential Pests on Horticultural Plants at the Agricultural Extension Center, Ngingas Village, Krian District, Sidoarjo Regency. : Identifikasi Hama Potensial pada Tanaman Hortikultura di Balai Penyuluhan Pertanian, Desa Ngingas, Kecamatan Krian, Kabupaten Sidoarjo. - Zahro, Balqis Ghaitza; Aditya, Haidar Fari; Kusuma, Ramadhani Mahendra (Journal of Applied Plant Technology, 2024)
This research aims to identify potential types of pests that attack horticultural plants at the Agricultural Extension Center (BPP) of Ngingas Village, Krian District, Sidoarjo Regency. This research uses a qualitative descriptive method by collecting data through direct observation, interviews with farmers and BPP staff. The types of plants that are the focus of this research are chilies, tomatoes and eggplant. The research results show that there are three main types of pests that attack horticultural plants in the area, namely whiteflies (Bemisia tabaci), mealybugs (Phenacoccus manihoti), and fruit flies (Bactrocera spp.). Symptoms of whitefly infestation include yellowing leaves and growth of sooty mold due to honeydew excretion. Mealybugs cause leaves to curl and turn yellow with white powder on the undersides of the leaves and stems. Fruit flies cause holes in the fruit, turning brownish in color, and the presence of larvae in the fruit.